PENGOLAHAN DAUN TALAS BENENG SEBAGAI ALTERNATIF PENGGANTI DAUN TEMBAKAU UNTUK BAHAN BAKU PRODUK ROKOK HERBAL: PENDAMPINGAN UMKM PADA POKTAN “TANI BAKO“ - Sunardi Sunardi; Basuki Rakhim Setya Permana (Gapenas Publisher, 2023)
This research aims to evaluate the potential of processing beneng taro leaves as an alternative to replace tobacco leaves in herbal cigarette production. The primary focus of the study is on supporting Micro, Small, and Medium Enterprises (MSMEs) in the